Study Of Economic Growth Factors To Evalate Economic Performance In Central Java Province - Prasetio Ariwibowo; Tjipto Djuhartono; Ai Annisa Utami (Program Studi Manajemen Universitas Muslim Maros, 2023)
The aim of this study is to analyze and assess the economic growth performance in the Central Java Province over the period spanning from 2019 to 2021. The research utilized the Financial Statements of the Regional Government of Central Java Province as the sample and population, covering the period from 2019 to 2022. The quantitative study utilizes a data analysis methodology that entails the examination of regional financial ratios, namely the Independence Ratio, Performance Ratio, SiLPA, PAD Growth, and APBD Growth. The study's findings suggest that the implementation of budget management in Central Java Province has been effective, resulting in the generation of money from multiple Regional Expenditure Budgets (APBD) that were authorized over the period from 2019 to 2022. Regarding poverty rates, the province observed a marginal rise from 10.8% in 2019 to 11.41% in 2020, afterwards followed by a further increase to 11.79% in 2021.